Factors Affecting Visual Inspection Examination of Acetic Acid (IVA) in Couples of Childbearing Age in the Working Area of UPT. Puskesmas Mandala Medan Year 2024 - Harahap, Aida Syahrani; Lumban Raja, Sarma; Nasution, Ramadhani Syafitri (PROMOTOR, 2024)
Visual Inspection of Acetic Acid (IVA) is an early detection of cervical cancer, the decline in IVA Test examinations in 2022 is from 154 people to 61 people in January to June 2023, where in half a year in 2023 the achievement of IVA Test examinations does not reach 50% of IVA examinations Test in 2022. The aim of the research is to analyze the factors that influence the visual inspection of acetic acid (VIA) in couples of childbearing age in the work area of UPT.Puskesmas Mandala Medan in 2023. This research is a combination of quantitative and qualitative research. The population was 259 people and the sample was 972 people. Quantitative data analysis using the chi-square test and multiple logistic regression and qualitative data analysis. The results of this study show that 38 people did not carry out IVA examinations with the chi-square test results showing the variables age, education, employment, knowledge, attitudes, culture and husband's support. The results of the multiple logistic regression test show that the knowledge variable has the most influence on visual inspection of acetic acid in women of childbearing age. The conclusion of this research is that there is an influence of age, education, work, knowledge, attitudes, culture and husband's support with visual inspection of acetic acid (IVA) on couples of childbearing age in the working area of UPT. Mandala Health Center Medan in 2023. It is recommended that UPT Mandala Health Center increase participation in providing training to health workers and be able to promote the VIA examination program and should involve husbands so that they can be enthusiastic in the VIA examination program and it is better for door to door health workers in providing VIA education